Effect of Polymer and Portland Cement on Strengthen Crushed Rock for Pavement Base - S. Chaiyaput; D. T. Bergado; J. Ayawanna (Lowland Technology International, 2019)
The effect of concurrent use of liquid polymer and Portland cement as a reinforced material in crushed rock pavement base was investigated in this work. The strength of polymer-treated crushed rock (treated crushed rock) and ordinary crushed rock (untreated crushed rock) were characterized and compared. In strength analysis, the California bearing ratios (CBR) of untreated and treated crushed rock were determined under unsoaked and soaked conditions to simulate post-flood pavement damage. The unconfined compressive strength (UCS) was evaluated under unsoaked conditions for 2h, 1-day, 3-day, 7-day, and 28-day curing periods. The results showed that the CBR of untreated and treated crushed rock under soaked and unsoaked conditions were positively correlated with dry density. The CBR under the unsoaked condition of untreated crushed rock was identical to that of treated crushed rock. Meanwhile, under the soaked condition, the CBR of treated crushed rock was twice as higher than the untreated crushed rock. The swelling indices were 0% for both untreated and treated samples. The UCS of treated crushed rock showed positively correlation with the curing time. The use of liquid polymer and Portland cement, therefore, improved the strength of crushed rock pavement base in which effectively mitigate the post-flood pavement damage.